Tranexamic acid in primary total knee arthroplasty without tourniquet: a randomized, controlled trial of oral versus intravenous versus topical administration - Wang, Duan (Sci Rep, 2018)
Abundant literature confirms that intravenous (IV) and intra-articular (IA) administration of tranexamic acid (TXA) reduces blood loss in total knee arthroplasty (TKA). Oral formulations of TXA exhibit profound cost-saving benefits. However, comparisons of the clinical efficacy among three different modalities of TXA administration have not been previously investigated in the setting of TKA with no closed suction drain and tourniquet. A total of 180 patients undergoing TKA were randomized to receive 2-g oral TXA 2 hours preoperatively, 20-mg/kg IV TXA 5 minutes prior to incision, or 2-g IA TXA. The primary outcome was 72-hour blood loss. Secondary outcomes were reductions in hemoglobin, the rate of transfusions, and adverse events. No significant differences were identified with regard to the mean 72-hour blood loss among the three groups (1003 mL in oral group, 1108 mL in IV group, and 1059 mL in IA group, respectively). Similarly, hemoglobin reduction was equivalent among the groups. Only one patient in IV group exhibited deep venous thrombosis. No difference was identified regarding transfusion rates. Oral TXA results in similar blood loss in TKA, with a profound cost-saving benefit, compared with the IA and IV formulations.